ANALISA PERANCANGAN SISTEM TEST MINAT DAN BAKAT DALAM MENENTUKAN JURUSAN CALON MAHASISWA UNTUK MENINGKATKAN KUALITAS KERJA KARYAWAN - Pakpahan, Roida; Nasila, Faziah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Major selection is a key aspect in determining the direction of education and career of prospective new students when starting the process of enrolling in higher education. Generally, major selection is done through an interest and aptitude test during the process of selecting majors and study programs. Interest and aptitude tests are important factors in supporting students' potential and future careers. In some universities, major selection is still done manually, one of which is through edufair. As a result, during the new student admission process, service is less than optimal, with many prospective students waiting in line. However, due to limited time and human resources, services cannot run smoothly. To overcome these various obstacles, a faster and more effective solution is needed in the new student admission process. The purpose of this study is to analyze the implementation of an online interest and aptitude test system in the process of selecting majors and study programs for new students to improve the quality of employee work using the Rapid Application Development method. The results show that the implementation of an online interest and aptitude test system is a solution in the process of providing recommendations for majors and study programs for prospective new students. The system can provide relevant information for prospective students according to their interests and potential. On the other hand, an online-based system can improve the quality of university employee service because employee work activities become more practical and efficient.